Answer:
x = -3
Step-by-step explanation:
expand -23x + 36 = 105
subtract 36 from both sides -23x +36 -36 = 105 - 36
Simplify -23x = 69
Divid both sides by -23: -23x / - 23 = 69 / -23
x = -3
The solution to given system of equations is (x, y) = (2, -1)
<em><u>Solution:</u></em>
Given system of equations are:
-1x + 2y = -4 -------- eqn 1
4x + 3y = 5 ------- eqn 2
We can solve the above system of equations by elimination method
<em><u>Multiply eqn 1 by 4</u></em>
4(-1x + 2y = -4)
-4x + 8y = -16 ------ eqn 3
<em><u>Add eqn 2 and eqn 3</u></em>
4x + 3y = 5
-4x + 8y = -16
( + ) --------------------
0x + 11y = -16 + 5
11y = -11
y = -1
<em><u>Substitute y = -1 in eqn 1</u></em>
-1x + 2(-1) = -4
-x -2 = -4
-x = -4 + 2
-x = -2
x = 2
<em><u>Check the answer:</u></em>
Substitute x = 2 and y = -1 in eqn 2
4x + 3y = 5
4(2) + 3(-1) = 5
8 - 3 = 5
5 = 5
Thus the obtained answer is correct
Thus the solution to given system of equations is (x, y) = (2, -1)
Answer:
22
Step-by-step explanation:
The y values increase by 2 every time so 18+2=22
Answer to the question
C. Lungs
Answer:
where is the expression??